S76 "Straight to CT" in Primary Care – Improving the Lung Cancer Patient Journey. (12th November 2015) - Nanapragasam, A; Maddock, N; McIver, A; Smyth, C; Walshaw, MJ
Abstract : Although the advent of rapid access secondary care services has shortened the wait to timely diagnosis in lung cancer, significant delays and congestion can still occur through patients needing to attend clinic before appropriate investigations are organised. To circumvent this, with primary care colleagues we designed a "straight to CT" system where if a general practitioner is concerned about a patient, or a chest X-ray in the community or emergency department shows suspicious changes, the radiology department automatically offers the patient a CT scan to be performed within 72 h with a same day report. This allows the primary care clinician to reassure patients with normal scans, or where necessary direct appropriately patients with scans showing non-malignant abnormalities. Patients with scans showing possible malignancy are intercepted by the lung cancer team who then organise appropriate further management. We replaced our one stop rapid access lung cancer clinic with this new service in January 2014 and have now reviewed its use one year on. 468 patients from the local community were eligible for the "straight to CT" service. Of the 246 with a coded X-ray, 222 underwent a 72-hour CT scan (18 of the reminder declined or were not contactable), and of these 127 (57%) showed suspicious abnormalities and were intercepted by the lung cancer team. Of the 222 referred by a concerned clinician, 177 underwent a 72-hour scan (of the remainder 19 were not contactable or declined and the rest were deemed inappropriate) and 60 of these (34%) showed suspicious changes and were intercepted by the lung cancer team. Overall, 401 72-hour scans were performed in 2014: this is similar to the number of scans performed (402) in 2013 using the traditional rapid access clinic model. As well as empowering primary care, by preventing unnecessary clinic attendance this innovative service has significantly reduced costs and by bringing forward investigations has reduced the lead time to diagnosis (to a mean of 19 days) in our patients. Furthermore, fears that such a service might increase unnecessarily the number of CT scans performed have proved groundless. We recommend the use of such a service to colleagues to aid timely and economical investigation of patients with a suspected diagnosis of lung cancer.